MENINGKATKAN HASIL BELAJAR SISWA MELALUI PEMBELAJARAN DENGAN MODEL DISCOVERY LEARNING PADA SISWA KELAS X MIPA 5 SMA N 1 BANTUL TAHUN PELAJARAN 2018/2019 - Sutrisno Sutrisno (Ideguru: Jurnal Karya Ilmiah Guru, 2019)
This study aims (1) to describe the learning process with Discovery Learning models among students; and (2) Improve the learning outcomes in subject of Bahasa Indonesia by application of discovery learning models. The subjects of this study were students of class X MIPA 5 SMA N 1 Bantul at 2018/2019 Academic Year. The study was conducted in three months from January to the end of March 2019. This study was a classroom action research (CAR), carried out in two cycles. Each cycle consists of four activities: (1) planning, (2) implementation, (3) observation, and (4) reflection. There are five types of data collection techniques used in this study, i.e. (1) observation, (2) questionnaire, (3) guided interviews, and (4) documentation. The results of this study show that (1) Discovery learning learning models improved teacher performance in learning, improved the performance of students in learning, and obtained excellent responses from students; (2) Implementation of discovery learning models improved student learning outcomes. The average value of student learning outcomes with the discovery learning model in cycle I was 82 with sufficient predicate, then increased to 94 in cycle II with very good predicate. The learning completeness in cycle I was 81.25% and increased to 100% in cycle II.